2018
DOI: 10.1103/physrevb.97.045411
|View full text |Cite
|
Sign up to set email alerts
|

Spin transport in two-layer-CVD-hBN/graphene/hBN heterostructures

Abstract: We study room-temperature spin transport in graphene devices encapsulated between a layer-by-layer-stacked two-layer-thick chemical vapor deposition (CVD) grown hexagonal boron nitride (hBN) tunnel barrier, and a few-layer-thick exfoliated-hBN substrate. We find mobilities and spin-relaxation times comparable to that of SiO 2 substrate-based graphene devices, and we obtain a similar order of magnitude of spin relaxation rates for both the Elliott-Yafet and D'Yakonov-Perel' mechanisms. The behavior of ferromagn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…In this device, the reversal of the magnetization direction of the ferromagnet leads to a sign change of the nonlocal resistance. Under experimental conditions, 42,43 this nonlocal resistance change ∆R nl = R nl (⇑) − R nl (⇓) can reach tens of Ohms (Ω) and is easily detectable. The second type of device is depicted in Panel b).…”
Section: Fig 7: a Four-terminal Geometry Involving Two Nodesmentioning
confidence: 99%
“…In this device, the reversal of the magnetization direction of the ferromagnet leads to a sign change of the nonlocal resistance. Under experimental conditions, 42,43 this nonlocal resistance change ∆R nl = R nl (⇑) − R nl (⇓) can reach tens of Ohms (Ω) and is easily detectable. The second type of device is depicted in Panel b).…”
Section: Fig 7: a Four-terminal Geometry Involving Two Nodesmentioning
confidence: 99%
“…To this end, the hybridization of g-C 3 N 4 with other functional materials, including fullerenes, has been developed in recent years and appears feasible since the polymeric nature of g-C 3 N 4 renders the chemical structure flexible. [68][69][70][71][72] For these graphene-analogous 2D nanomaterials, especially g-C 3 N 4 and the TMD MoS 2 , no Review has reported their hybridization with fullerenes, which is crucial for understanding such intriguing 0D-2D hybrid systems. [56][57][58][59][60] MoS 2 , consisting of hexagonal rings with Mo and S atoms alternately located at the hexagon corners, is the most representative TMD with a direct band gap in monolayer form and high in-plane carrier mobility, thus being suitable for versatile applications in electro and photocatalysis, photovoltaics, and photoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, theoretical calculation shows that the spin injection efficiency can reach 100% with the increase in the hBN's thickness by using a Ni electrode [68], which has a good lattice match with both the graphene and the hBN. Experimentally, both of exfoliated hBN [72,73] and CVD-hBN [74][75][76][77] have been extensively studied as a tunnel barrier. What's more, it was indicated that a thicker hBN tunneling layer could achieve higher spin polarization [78].…”
Section: Electrical Injection In 2d Materialsmentioning
confidence: 99%